2010
DOI: 10.1007/s12011-010-8854-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lanthanum on Calcium and Magnesium Contents and Cytoplasmic Streaming of Internodal Cells of Chara corallina

Abstract: Biological and environmental effects of lanthanide series of elements have received much attention recently due to their wide applications. In this study, effects of La(3+) treatments on calcium and magnesium concentrations as well as cytoplasmic streaming of internodal cells of Chara corallina were investigated. At all treatment concentrations (10, 100, and 1,000 μM), La(3+) significantly decreased calcium concentrations in the cell-wall fractions after 5-h treatments. Calcium concentrations in the cell conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Only recently, studies have focused on the ecological effects of Ln and their potential to affect life (Li et al, 2010 , and references therein). Those experiments have shown that effects of Ln on plant growth are diverse and dose–response relationships are complicated (Li et al, 2011 ). Algae, as primary producers and the basis of many food webs, are important and sensitive organisms with opportunities for exposure to Ln, although the effects of Ln on algae are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently, studies have focused on the ecological effects of Ln and their potential to affect life (Li et al, 2010 , and references therein). Those experiments have shown that effects of Ln on plant growth are diverse and dose–response relationships are complicated (Li et al, 2011 ). Algae, as primary producers and the basis of many food webs, are important and sensitive organisms with opportunities for exposure to Ln, although the effects of Ln on algae are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In these publications, different metabolic processes were involved, such as photosynthesis (light and dark reactions), respiration, nitrogen metabolism, and oxidative stress (Table 1 ). In one unique study, based on the green macroalga Chara corallina , lower concentrations of La 3+ were shown to partially compensate for Ca 2+ -deficiency, thus permitting cytoplasmic streaming (Li et al, 2011 ). To our knowledge, there are no microalgal studies dealing with metal alleviation by Ln.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, La 3+ blocks calcium channels on the cell membrane; however, the results of La 3+ treatment in this study regarding the effects of cytoplasmic calcium were inconsistent. It has been suggested that a significant reduction in cytoplasmic Ca 2+ concentration might be due to the inhibition of extracellular calcium influx 47 . However, some studies suggest that although La 3+ inhibits extracellular calcium influx, it can also cause stored intracellular calcium to be released, thereby increasing Ca 2+ cytoplasmic concentration 48 .…”
Section: Discussionmentioning
confidence: 99%
“…This study summarizes knowledge of positive and toxic effects of lanthanides on algae in order to better elucidate their biological roles. Various applications and methods of use, including the possibility of remediation and lanthanide recycling are also suggested [8][9][10]. The study arrived at a brief conclusion, which stated that algae are very important, being at the very beginning of the food chain.…”
Section: Summary Of the Bookmentioning
confidence: 99%